2022
DOI: 10.1039/d2bm00756h
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary delivery of curcumin-loaded glycyrrhizic acid nanoparticles for anti-inflammatory therapy

Abstract: Acute lung injury (ALI) is an inflammatory disease in the lungs. Curcumin (Cur) has protective effects in ALI animal models. However, Cur is a hydrophobic drug and administration into the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 23 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…GA can also be used as a multi-functional drug carrier to enhance the activity of other drugs ( Selyutina and Polyakov, 2019 ). Chunxian Piao ( Piao et al, 2022 ) prepared curcumin-loaded acidic nanoparticles by self-assembly method. The results showed that compared with glycyrrhizic acid + curcumin, curcumin-loaded glycyrrhizic acid nanoparticles had higher anti-inflammatory effects in vitro-in vivo by reducing pro-inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…GA can also be used as a multi-functional drug carrier to enhance the activity of other drugs ( Selyutina and Polyakov, 2019 ). Chunxian Piao ( Piao et al, 2022 ) prepared curcumin-loaded acidic nanoparticles by self-assembly method. The results showed that compared with glycyrrhizic acid + curcumin, curcumin-loaded glycyrrhizic acid nanoparticles had higher anti-inflammatory effects in vitro-in vivo by reducing pro-inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…Glycyrrhizin can be effective in drug delivery applications by enhancing the therapeutic activity of other drugs ( Piao et al, 2022 ). Its amphiphilic properties enable it to form self-associates like dimers and micelles and bind to hydrophobic drugs by supramolecular complexes ( Sun et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Micelles are spherical structures with hydrophobic cores and hydrophilic shell . The shell makes them soluble in water, enabling intravenous delivery, while the core is loaded with hydrophobic therapeutic agents such as curcumin, doxorubicin, and others. In this study, the anticancer therapeutic drug Temozolomide (TMZ) for GBM was loaded into T7-chol. TMZ serves as a chemotherapeutic agent for treating GBM, but has limitations including a short half-life of 1.8 h, susceptibility to degradation under physiological conditions, and rapid metabolism at pH (>7.0). This suggests that TMZ-loaded T7-chol micelles may mitigate degradation under physiological conditions, thereby potentially enhancing drug delivery efficiency.…”
Section: Introductionmentioning
confidence: 99%